2017
DOI: 10.5194/cp-13-1269-2017
|View full text |Cite
|
Sign up to set email alerts
|

The De Long Trough: a newly discovered glacial trough on the East Siberian continental margin

Abstract: Abstract. Ice sheets extending over parts of the East Siberian continental shelf have been proposed for the last glacial period and during the larger Pleistocene glaciations. The sparse data available over this sector of the Arctic Ocean have left the timing, extent and even existence of these ice sheets largely unresolved. Here we present new geophysical mapping and sediment coring data from the East Siberian shelf and slope collected during the 2014 SWERUS-C3 expedition (SWERUS-C3: Swedish -Russian -US Arcti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…However, despite attempts to find evidence for a significant LGM ice sheet in this region (Grosswald and Hughes, 2002), none has been found (Brigham-Grette et al, 2003;Gualtieri et al, 2003;Stauch and Lehmkuhl, 2010; Clark, 2011, 2012;Jakobsson et al, 2014). A large ice sheet existed within the region at some point during the Pleistocene, but all evidence for this ice appears to predate the LGM (Niessen et al, 2013;O'Regan et al, 2017). Similarly, parts of the Arctic Ocean appear to have supported grounded ice, in the form of extensive ice shelves (Gasson et al, 2018).…”
Section: Updated Missing Ice Estimate and Directions Forwardmentioning
confidence: 99%
“…However, despite attempts to find evidence for a significant LGM ice sheet in this region (Grosswald and Hughes, 2002), none has been found (Brigham-Grette et al, 2003;Gualtieri et al, 2003;Stauch and Lehmkuhl, 2010; Clark, 2011, 2012;Jakobsson et al, 2014). A large ice sheet existed within the region at some point during the Pleistocene, but all evidence for this ice appears to predate the LGM (Niessen et al, 2013;O'Regan et al, 2017). Similarly, parts of the Arctic Ocean appear to have supported grounded ice, in the form of extensive ice shelves (Gasson et al, 2018).…”
Section: Updated Missing Ice Estimate and Directions Forwardmentioning
confidence: 99%
“…Jakobsson and coauthors provide evidence of a kilometer-thick ice shelf covering the entire central Arctic Ocean and extending up to present-day New Siberian Islands during the glacial maximum (Marine Isotope Stage 6, 140 ka BP) [62]. Moreover, another study reported on a glacially excavated trough discovered on the ESAS (De Long Trough), which is also dated to Marine Isotope Stage 6 [64]. However, it seems reasonable to assume the modern exaration processes considering the sedimentation rates (from 0.12 to 1.3 mm year −1 ) estimated for this region in previous studies [11,65].…”
Section: Grain Size Distribution Along the Studied Profilementioning
confidence: 96%
“…This assumption is required because we are not able to distinguish pre-LGM sediments in our data even though we acknowledge that older (pre-LGM) sediment is sometimes preserved in these settings (e.g. Hooke and Elverhøi, 1996;Aarseth, 1997;O'Regan et al, 2017;Jennings et al, 2019). This assumption is justified by theoretical studies of glacial erosion/sediment transport, which are based on observations, that most often suggest that fjords are rapidly and fully excavated during glacial advances (Powell, 1984;Aarseth, 1997;Hjelstuen et al, 2009).…”
Section: Glacial Volumes Fluxes and Erosion Ratesmentioning
confidence: 98%
“…Where such flow deposits are prolific and occur at the seafloor, they are easily identified as smooth, lobate features in front of known grounding-zone positions marked by terminal moraines (e.g. Ottesen and Dowdeswell, 2006;Flink et al, 2015) or GZWs (e.g. Bjarnardóttir et al, 2013;Esteves et al, 2017).…”
Section: Large Subglacial Landforms: Grounding-zone Wedges (Gzws)mentioning
confidence: 99%